Radiological Evaluation of Coronary Artery Anatomical Variations and Their Association with Coronary Artery Disease in the Pakistani Population - Amir Khan, Mohammad; Razaq, Kanza; Younis, Khawaja Adnan; Qayyum, Saad; Afzal, Asifa; Fatima, Sana (Journal of Neonatal Surgery, 2025)
Background: Coronary artery disease (CAD) remains a leading cause of morbidity and mortality worldwide. With advances in radiological imaging techniques, particularly coronary angiography and CT coronary angiography, coronary artery anatomical variations are increasingly recognized as important determinants of cardiovascular outcomes. Objective: To evaluate the association between radiologically detected coronary artery anatomical variations and the risk of CAD in a Pakistani population. Methods: A cross-sectional analytical study was conducted on 220 patients undergoing diagnostic coronary angiography and radiological assessment of coronary anatomy. Coronary artery variations, including anomalies of origin, course, and dominance patterns, were identified through imaging. CAD severity was assessed based on ≥50% luminal stenosis. Statistical analysis included chi-square testing and logistic regression. Results: Coronary artery variations were identified in 34.5% of patients using radiological imaging modalities. The presence of these variations was significantly associated with CAD (p < 0.001). Patients with anatomical variations demonstrated higher odds of significant CAD (OR = 2.38, 95% CI: 1.45–3.91). Conclusion: Radiologically detected coronary artery anatomical variations are significantly associated with increased risk and severity of CAD. Incorporating advanced cardiac imaging techniques into routine evaluation may improve early detection and risk stratification in clinical practice.